The jurisprudential practice of the International Criminal Court – as I saw it - Kovács, Péter (2025)
This reflective volume offers a compilation of old and new pieces of Prof. Dr. Péter Kovács on the International Criminal Court. The book offers insights drawn from his time on the bench of the Court at the end of his mandate (2015-2024) from a personal perspective. Therefore, the book provides a holistic approach to the role and jurisprudence of the Court, reflecting on its historical perspective, its place in the international legal order, and various aspects of its jurisprudence, such as children in the practice of the Court, victims’ rights, interim measures, and linguistic issues. The volume thus provides the quintessence of the scientific reflections of Prof. Dr. Kovács on the International Criminal Court and its contribution to the development of international criminal law and public international law.